The Correlation of Body Condition Score (BCS) to Lust Value in Friesian Holstein Crosbred Dairy Cows at KAN JABUNG - Nurkholis; Octaviani, Wanda Tita; Nurfitriani, Rizki Amalia; Rukmi, Dyah Laksito (Politeknik Negeri Jember, 2025)
This study aimed to determine the relationship between body condition score (BCS) and estrus expression. The study was conducted by measuring BCS and observing estrus expression in the vulva (color change, swelling, increased temperature, and mucus secretion) before artificial insemination. BCS was assessed using a 5-point interval scale. This study was conducted on 20 Friesian Holstein crossbreed dairy cows that showed signs of estrus and had given birth (first lactation) or were older than 3 years. There was a correlation between BCS and several estrus indicators in the vulva: color change (r=0.70), increased temperature (r=0.91), mucus secretion (r=0.77), and swelling (r=0.50). Cows with a low BCS showed poor estrus quality, while cows with a moderate BCS showed more pronounced estrus symptoms. This suggests that inadequate nutrition in cows with a low BCS can lead to hormonal imbalance and suboptimal reproductive performance. Therefore, it is important to increase livestock farmers' awareness of the importance of providing sufficient and quality feed to meet livestock nutritional needs and achieve optimal reproductive performance.